Diffusion tensor imaging of the human calf: Variation of inter‐ and intramuscle‐specific diffusion parameters. Issue 4 (2nd February 2017) - Schlaffke, Lara; Rehmann, Robert; Froeling, Martijn; Kley, Rudolf; Tegenthoff, Martin; Vorgerd, Matthias; Schmidt‐Wilcke, Tobias
Abstract : Purpose: To investigate to what extent inter‐ and intramuscular variations of diffusion parameters of human calf muscles can be explained by age, gender, muscle location, and body mass index (BMI) in a specific age group (20–35 years). Materials and Methods: Whole calf muscles of 18 healthy volunteers were evaluated. Magnetic resonance imaging (MRI) was performed using a 3T scanner and a 16‐channel Torso XL coil. Diffusion‐weighted images were acquired to perform fiber tractography and diffusion tensor imaging (DTI) analysis for each muscle of both legs. Fiber tractography was used to separate seven lower leg muscles. Associations between DTI parameters and confounds were evaluated. All muscles were additionally separated in seven identical segments along the z‐axis to evaluate intramuscular differences in diffusion parameters. Results: Fractional anisotropy (FA) and mean diffusivity (MD) were obtained for each muscle with low standard deviations (SDs) (SDFA : 0.01–0.02; SDMD : 0.07–0.14(10 −3 )). We found significant differences in FA values of the tibialis anterior muscle (AT) and extensor digitorum longus (EDL) muscles between men and women for whole muscle FA (two‐sample t ‐tests; AT: P  = 0.0014; EDL: P  = 0.0004). We showed significant intramuscular differences in diffusion parameters between adjacent segments in most calf muscles ( P < 0.001). Whereas muscle insertions showed higher (SD 0.03–0.06) than muscle bellies (SD 0.01–0.03), no relationships between FA or MD with age or BMI were found. Conclusion: Inter‐ and intramuscular variations in diffusion parameters of the calf were shown, which are not related to age or BMI in this age group. Differences between muscle belly and insertion should be considered when interpreting datasets not including whole muscles. Level of Evidence: 3 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2017;46:1137–1148.